Effects of Participant Engagement on Prosodic Prominence. Issue 3 (3rd April 2018) - Buxó-Lugo, Andrés; Toscano, Joseph C.; Watson, Duane G.
Abstract : It is generally assumed that prosodic cues that provide linguistic information, like discourse status, are driven primarily by the information structure of the conversation. This article investigates whether speakers have the capacity to adjust subtle acoustic-phonetic properties of the prosodic signal when they find themselves in contexts in which accurate communication is important. Thus, we examine whether the communicative context, in addition to discourse structure, modulates prosodic choices when speakers produce acoustic prominence. We manipulated the discourse status of target words in the context of a highly communicative task (i.e., working with a partner to solve puzzles in the computer game Minecraft) and in the context of a less communicative task more typical of psycholinguistic experiments (i.e., picture description). Speakers in the more communicative task produced prosodic cues to discourse structure that were more discriminable than those in the less communicative task. In a second experiment, we found that the presence or absence of a conversational partner drove some, but not all, of these effects. Together, these results suggest that speakers can modulate the prosodic signal in response to the communicative and social context.